Perceptions of the right to language in the Nahuas of Santa Ana Tlacotenco (Raíces: Revista de Ciencias Sociales y Políticas, 2022)
This article analyzes some perceptions that the Nahua community of Santa Ana Tlacotenco, Mayor´s Offi ce Milpa Alta, in Mexico City has regarding the right to language. This right as a positive Mexican right is not only interpreted from its legal understanding, but requires, in addition to the signifi cance of the originarl peoples, for the latter, the importance of this study. Knowing the perceptions that the Nahuas of Santa Ana Tlacotenco have regarding this right, establishes as one of the results that the rigth to language is understood by the actors of this research as a constitutional right that entails an asymmetric power relationship between the Satate Mexican and indigenous people; a right tha juridically appears to be neutral, but with which the power of the Satate continues to be strengthened over cultural assets such as the languages of minority groups; therefore, at the social level this right is perceived as a right with political content.Theoretically, this research is based on Legal Realism and Critical Theory of Law; and is characterized by being a qualitative study carried out during 2019 and 2020, whose database was built from semi-structured interviews and fi eld observations, which were analyzed through the Grounded Theory Method of Strauss and Corbin (2002).
Keywords: Right to language; Nahuas; Legal Realism; Critical Theory of Law